Developments of pH responsive biodegradable monitoring film based on poly(vinyl alcohol) incorporated with Sappan heartwood extract for food packaging applications - Worraphol Nansu; Gareth Ross; Sukunya Ross; Nungruthai Suphrom; Sararat Mahasaranon (AIMS Materials Science, 2023)
The major problem leading to substantial waste in the food industry is the spoilage of food products during transportation and storage periods. Consequently, the scope of this research focuses on the development and preparation a pH responsive monitoring films based on biodegradable materials of poly(vinyl alcohol) (PVA) and natural colorant extract from Caesalpinia sappan L. heartwood (SP). These monitoring films were prepared by a solution casting method and the film stability was improved by crosslinking with citric acid (CA). The red tone of monitoring film without CA was observed, while the crosslinked monitoring film showed a yellow color, which occurs from the structural change of brazilin (structure presenting in SP) to brazilein under acidic conditions. From the SEM and FTIR results, the monitoring film showed high compatibility between phases, improvements in light barrier properties and good WVTR performance. The tensile strength and elongation at break were slightly increased. For pH responsive properties, the monitoring films showed a high response with NH3 gas detection with the change in color from a yellow tone to a red tone. These results indicated that the monitoring films have potential to be applied as food packaging for meat, fish, pork, chicken, and other foods that generate ammonium gas during spoilage. Therefore, these high stable, and non-toxic biodegradable PVA films that incorporated with SP extract and crosslinked by CA have the potential to be used for food spoilage detection in packaging.